Meursault, contre-enquête de K. Daoud et l’Étranger d’A. Camus : transposition/déviation au nom de Moussa - Tahar Zouranene (Multilinguales)
Through this article, we have attempted to suggest a reading of Kamel Daoud’s novel Meursault, Contre-enquête (2013) in order to show this surplus of meaning that the author did not intend to convey in his palimpsest-work of Camus’ L’Étranger. We have first identified the elements explicitly borrowed from Camus’ novel, and then their deviation.These multiple intertextual links in their transposition / deviation have allowed us to shed light on an "introductory" main character, opposite Meursault, who like the latter, is the keystone of the novel. His liminality places him on the threshold of all the truths and all the political and polemical assertions that surrounded the Camusian novel and its author, and opposite to what the "Contre-enquête", of the Daoudian title, predicted. Daoud’s novel makes a transfer of the socio-historical context of Camus’s text, from the period of colonization of Algeria to post-independence, which permits his return to the Camusian novel in its socio-text dimension involving its co-text. We can then prove that it is this transfer carried out by a scriptable text that directs the complex re-reading of Camus’ novel.